Shear-induced softening of nanocrystalline metal interfaces at cryogenic temperatures. (15th January 2018) - Chandross, Michael; Curry, John F.; Babuska, Tomas F.; Lu, Ping; Furnish, Timothy A.; Kustas, Andrew B.; Nation, Brendan L.; Staats, Wayne L.; Argibay, Nicolas
Abstract: We demonstrate inverse Hall-Petch behavior (softening) in pure copper sliding contacts at cryogenic temperatures. By kinetically limiting grain growth, it is possible to generate a quasi-stable ultra-nanocrystalline surface layer with reduced strength. In situ electrical contact resistance measurements were used to determine grain size evolution at the interface, in agreement with reports of softening in highly nanotwinned copper. We also show evidence of a direct correlation between surface grain size and friction coefficient, validating a model linking friction in pure metals and the transition from dislocation mediated plasticity to grain boundary sliding. Graphical abstract: Image 2